Design anthropology : theory and practice - Gunn, Wendy, ....-; Otto, Ton., ....-; Smith, Rachel Charlotte, ....- (London : Bloomsbury, 2013)
Design is a key site of cultural production and change in contemporary society. Anthropologists have been involved in design projects for several decades but only recently a new field of inquiry has emerged which aims to integrate the strengths of design thinking and anthropological research. This book is written by anthropologists who actively participate in the development of design anthropology. Comprising both cutting-edge explorations and theoretical reflections, it provides a much-needed introduction to the concepts, methods, practices and challenges of the new field. Design Anthropology moves from observation and interpretation to collaboration, intervention and co-creation. Its practitioners participate in multidisciplinary design teams working towards concrete solutions for problems that are sometimes ill-defined. The authors address the critical potential of design anthropology in a wide range of design activities across the globe and query the impact of design on the discipline of anthropology. This volume will appeal to new and experienced practitioners in the field as well as to students of anthropology, innovation, science and technology studies, and a wide range of design studies focusing on user participation, innovation, and collaborative research.
Includes bibliographical references and index.
Keywords: Design -- Anthropological aspects; Art and anthropology; Art and design